IMPORTANCE OF CATERING ENTERPRISES' CLASSIFICATION IN SERVICE QUALITY ASSESSMENT FROM THE CUSTOMER'S POINT OF VIEW. CASE OF REZEKNE CITY. (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2019)
There are a lot of catering companies offering their services on the market, hence, there is a fierce competition between them. It is essential to provide customers with the appropriate level of service they expect from the respective caterer (restaurant, café, bar, etc.). The aim of the paper is to explore the importance of classification of the catering companies in service quality assessment from the customer's point of view in Rezekne city. The paper is developed within the framework of the RTA scientific grant "Quality Assessment of Rezekne City Catering Companies". Within the grant project, an expert questionnaire was developed to carry out quality assessment of Rezekne city catering enterprises. As a result of the research, it was concluded that the customer service in Rezekne city differs depending on the type of the catering establishment. The monographic, logical constructive, and graphic method, as well as the method of observation (expert questionnaires) were used for the research.